2022
DOI: 10.1111/jan.15258
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review and meta‐analysis on the effectiveness of web‐based psychosocial interventions among patients with colorectal cancer

Abstract: Aims: To synthesize the effectiveness of web-based psychosocial interventions on self-efficacy, anxiety, depression, quality of life (QoL), non-specific psychological and cancer-specific distress among patients with colorectal cancer (CRC). Design: A systematic review and meta-analysis. Data sources: Six databases (PubMed, PsycINFO, Embase, Scopus, CINAHL and CNKI) were searched from inception to December 2021. Review methods: Experimental/quasi-experimental studies involving patients with CRC for the improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…The remaining 134 reviews met eligibility criteria and were included in the synthesis. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 …”
Section: Resultsmentioning
confidence: 99%
“…The remaining 134 reviews met eligibility criteria and were included in the synthesis. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 …”
Section: Resultsmentioning
confidence: 99%
“…Overall ratings of confidence were applied to the reviews 20 . Therefore, the rating of confidence was high for three reviews, 24,27,34 moderate for 2, 25,28 low for 3, 18,22,35 and critically low for 12 19–21,23,26,29–33,36,37 …”
Section: Resultsmentioning
confidence: 99%
“…Digital interventions showed mixed results for emotional variables. Even if some studies tended to show a positive effect of these interventions on anxiety (app‐based interventions 21,29 ) and depression (web‐based 19,20,25,30,34 and app‐based 29 interventions), the general tendency was to not observe statistically significant effects 18,19,23,27,29,31,34 . However, regarding psychological distress, studies showed positive effects for both web‐based and app‐based interventions 25–27,29,36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations